Intestinal barrier dysfunction, endotoxemia, and gastrointestinal symptoms: the 'canary in the coal mine' during exercise-heat stress? - Lambert, G. P. (Thermoregulation and human performance. Physiological and biological aspects, 2008)
Reduced intestinal blood flow and high intestinal temperatures during exercise-heat stress can lead to intestinal barrier dysfunction. Such dysfunction may increase intestinal permeability to endotoxin. During exercise-heat stress, intestinal barrier dysfunction and endotoxemia can produce gastrointestinal symptoms and increased production of pro-inflammatory cytokines. Such problems may be a warning sign (`canary in the coal mine`) for the onset of exertional heat stroke. Failure to heed such a warning may culminate in problems indicative of exertional heat stroke such as circulatory collapse and multiple organ failure. Prior exposure to exercise-heat stress may, however, be a protective mechanism.